Effect of conventional and microwave heating treatment on antioxidant activity of quinoa protein after simulated gastrointestinal digestion. (30th July 2023) - Cao, Hongwei; Huang, Qilong; shi, Junru; Guan, Xiao; Song, Hongdong; Zhang, Yu; Xie, Jian; Fang, Yong
Graphical abstract: Highlights: Microwave heating at 70 °C had highest digestion rate of quinoa protein. Microwave treatment led to unfolding and aggregation of quinoa protein. Microwave processing led to an increase in free amino acid and sulfhydryl content. Microwave treated quinoa protein hydrolysates showed higher antioxidant activity. Abstract: Effects of microwave and traditional water bath treatment at different temperatures (70, 80, 90 ℃) on in vitro digestion rate and antioxidant activity of digestion products of quinoa protein were investigated. The results indicated microwave treatment at 70 ℃ produced the highest quinoa protein digestion rate and the strongest antioxidant activities of its digestion products (P < 0.05), which was further verified by the results of free amino, sulfhydryl group, gel electrophoresis, amino acid profiles and the molecular weight distribution of the digestion products. However, limited exposure of active groups induced by water bath treatment might decrease the susceptibility of digestive enzymes and subsequently lower the digestibility and antioxidant activities of quinoa protein. The results suggested that a moderate microwave treatment could be used as a potential way to enhance the in vitro digestion rate of quinoa protein, as well as increase the antioxidant activities of its digestion products.